AKIBAT HUKUM DEBITUR WANPRESTASI DALAM PERJANJIAN KREDIT DENGAN JAMINAN CESSIE PADA PT. BANK MANDIRI (PERSERO) TBK. COMMERCIAL BANKING CENTER CABANG DENPASAR - Pradnyana Widiantara, I Wayan Gede; Suantra, I Nengah (Kertha Semaya : Journal Ilmu Hukum, 2013)
Bank as a financial institution can act as a source of funding, including in the form ofcredit. Lending is certainly a particular mechanism, one of them by treaty and isaccompanied with a guarantee. One form of credit guarantees is cessie. In execution of thecredit agreement, there is a possibility of either party in default or negligence of theobligations set forth and agreed upon in the loan agreement. The aim in this paper is todetermine whether the legal effect of the debtor defaults under the loan agreement withcessie collateral at PT. Bank Mandiri (Persero) Tbk. Commercial Banking CenterDenpasar Branch. The research method used in this paper is the empirical legal researchusing data collection techniques of observation, interviews and document research. The results obtained from this research show that the legal effect of the debtor defaults underthe loan agreement with cessie collateral at PT. Bank Mandiri (Persero) Tbk. CommercialBanking Center Denpasar Branch which will be the enactment of these credits to thecategory of bad loans that will be made loan resolution process by carrying out theexecutions of cessie collateral by way of sale under the hand and all costs with theircompensation in the form of fines arising from the expiry of the credit due to defaults arecharged to the debtor.
Keywords: Legal Effect, Default, Loan Agreement, Cessie Collateral